Usthaz M. A. M. Mansoor and his contribution to reforming Islamic thought in Sri Lanka: a critical appraisal - Mohamed Fouz, Mohamed Zacky; Ash-Sheikh Dr. M.J.M Arafath Careem, Ash-Sheikh Dr. M.J.M Arafath Careem; Ilyas, Ash-Sheikh Inaz (Mishkath Research Institute, 2025)
Beginning with the pioneering efforts of M. C. Siddi Lebbe in the late nineteenth century, Sri Lankan Muslim reformism has evolved through diverse phases of educational activism, socio-religious revival, legal reinterpretation, and public engagement. Usthaz M.A.M. Mansoor stands today as a significant and distinctive voice within this lineage. He represents both continuity and renewal: continuity in his deep rootedness in Islamic scholarship, and renewal through his commitment to addressing the pressing intellectual and social questions confronting Sri Lankan Muslims in the contemporary era. Seeking to reimagine the role of faith in a rapidly transforming national landscape, Usthaz Mansoor’s writings and public interventions extend the reformist vision beyond institutional critique and into the realms of moral rejuvenation, communal solidarity, and civic responsibility. His thought demonstrates a careful balance between fidelity to the Islamic scholarly tradition and an openness to the ethical, political, and social challenges of the present. In this sense, he continues and enriches the reformist project that earlier generations initiated, one that insists on the compatibility of Islamic authenticity with social progress, educational advancement, and national coexistence.